Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Explore thousands of questions and answers from knowledgeable experts in various fields on our Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Answer:
x=3y−1x=3y-1
x+2y=9x+2y=9
Replace all occurrences of xx with 3y−13y-1 in each equation.
Tap for fewer steps...
Replace all occurrences of xx in x+2y=9x+2y=9 with 3y−13y-1.
(3y−1)+2y=9(3y-1)+2y=9
x=3y−1x=3y-1
Add 3y3y and 2y2y.
5y−1=95y-1=9
x=3y−1x=3y-1
Solve for yy in the first equation.
Tap for fewer steps...
Move all terms not containing yy to the right side of the equation.
Tap for fewer steps...
Add 11 to both sides of the equation.
5y=9+15y=9+1
x=3y−1x=3y-1
Add 99 and 11.
5y=105y=10
x=3y−1x=3y-1
Divide each term by 55 and simplify.
Tap for fewer steps...
Divide each term in 5y=105y=10 by 55.
5y5=1055y5=105
x=3y−1x=3y-1
Cancel the common factor of 55.
Tap for fewer steps...
Cancel the common factor.
5y5=1055y5=105
x=3y−1x=3y-1
Divide yy by 11.
x=5,y=2
Step-by-step explanation:
please mark me as brainliest thank you
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.